Manipulation of room-temperature magnetic skyrmions in a van der Waals ferromagnet Fe3GaTe2 - Yanlong Yin; Minghe Liu; Wei Li; Wan Li; Mengting Zou; Si Wu; Weixing Xia; Baomin Wang (New Journal of Physics)
The magnetic skyrmion in two-dimensional van der Waals (vdW) ferromagnetic materials offer a feasible and robust platform for future spintronic applications, thanks to their atomic-scale interface and stacking structure. Recently, a room temperature vdW ferromagnet Fe _3 GaTe _2 (FGT) has been discovered, in which skyrmion lattice can be generated. In this work, we studied the evolution of stripe domains in FGT nanoflake at different temperatures and magnetic fields, confirming the Néel-type skyrmion through Lorentz transmission electron microscopy. We systematically explored the dependence of the size, density and stability of skyrmion on the thickness, temperature and magnetic field of the FGT nanoflake. This work provides a variety of experimental evidence to shed light on the potential application of two-dimensional vdW FGT for future spintronic devices.